Metabolismo e eficiência zootécnica de jundiás (Rhamdia quelen) alimentados com concentrados proteicos vegetais - Lovatto, Naglezi de Menezes (2012)
This work was conducted to evaluate the growth and metabolism of jundiá fed protein concentrates of sunflower meal and crambe as a substitute source of vegetable protein, 25 and 50% of animal protein. The work was divided into two distinct phases. The first consisted in obtaining and characterization of protein concentrates of sunflower meal and crambe methodology using concentration by isoelectric pH (Smith et al, 1946), with modifications. We obtained values of 51.42 and 50.37% crude protein and yield of 48.30 and 50.32% respectively. Regarding the profile of amino acids, the protein concentration in crambe meal increased levels of lysine and methionine in 50.29 and 122.00%, respectively. In sunflower protein concentrate increased by 41.5 and 186%. In the second phase the biological assay was conducted for 52 days in water recirculation system. We used 300 jundiás with average initial weight of 14.59 ± 0.18 g, these animals were housed in 15 experimental units of 280L net volume of each. The initial stocking density was 1.04 g fish / L water. We evaluated two levels (25 and 50%) partial replacement of protein coming from the flour meat and swine bone by protein concentrates in question. At the end of the period, there were no statistical differences for weight (W). The feed conversion ratio (FCR) was higher in the Control and CPFG-25% diets (P <0.05). There was no significant difference (P> 0.05) for specific growth rate (SGR), relative weight gain (RWG) e average daily gain (ADG). In relation to condition factor (CF), the highest values were found in the diet CPFG-25%. There was no statistical difference (P> 0.05) in dry matter, protein and crude protein deposited (CPD) in carcasses of animals subjected to different diets. We found a higher lipid content and total fat deposited (TFD) in the diet CPFG-50%. For carcass yield (CY) and digestive rates was not significant between the experimental diets. The activities of digestive enzymes trypsin and chymotrypsin showed no statistical differences in diets. There was no significant difference for any of the analyzed blood parameters (glucose, total circulating protein, albumin, cholesterol and triglycerides). The animals diet CPFG-25% had higher liver glycogen stock (p <0.05). It was found increased activity (p <0.05) of the enzyme glutamic-pyruvic transaminases (GPT) in animals of the control diet. Was observed increase in the concentration of free amino acids in fish fed diet CPFG- 25%. It can be concluded that the use of protein concentrates of sunflower meal and crambe meal did not affect growth and weight gain of fish as well as metabolism. The protein concentrate of sunflower meal was more metabolically efficient than crambe meal. The animals fed diet CPFG-25% had improved metabolic efficiency of use of the ingredients.